2017
DOI: 10.1111/dar.12599
|View full text |Cite
|
Sign up to set email alerts
|

Research into action? The Eastside Illicit Drinkers Group for Education's (EIDGE) experiences as a community‐based group in Vancouver, Canada

Abstract: The Eastside Illicit Drinkers Group for Education has been supportive of research dedicated to establishing the effectiveness of Managed Alcohol Programs since its inception. Dedicated funding for MAPs in Vancouver, British Columbia is contingent on the research demonstrating that alcohol-related harms are reduced while participating in a Managed Alcohol Program. The Eastside Illicit Drinkers Group for Education understands the need for evidence-based research but we are critical of how much research is needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Just as in the present study, this research underscored the importance of implementing a caring and compassionate approach toward people experiencing homelessness-an approach that includes taking the time to get to know each person; listening to them; letting them rest; and adjusting to their pace, needs, and aspirations (Evans et al, 2015). In a similar vein, other authors also pointed out how the incorporation of experiential knowledge on homelessness into the development and design of future wet services is a promising way to ensure that these services meet the needs of those they set out to assist (Brown et al, 2018;Hanna & Burke, 2019).…”
Section: Adapting Institutional Regulations and Mandates To Needsmentioning
confidence: 99%
“…Just as in the present study, this research underscored the importance of implementing a caring and compassionate approach toward people experiencing homelessness-an approach that includes taking the time to get to know each person; listening to them; letting them rest; and adjusting to their pace, needs, and aspirations (Evans et al, 2015). In a similar vein, other authors also pointed out how the incorporation of experiential knowledge on homelessness into the development and design of future wet services is a promising way to ensure that these services meet the needs of those they set out to assist (Brown et al, 2018;Hanna & Burke, 2019).…”
Section: Adapting Institutional Regulations and Mandates To Needsmentioning
confidence: 99%
“…The AKE project and writing of the VAS originated as an initiative of EIDGE, a peer-led education and advocacy group for illicit drinkers operated under the umbrella of VANDU. Illicit drinkers are people who drink alcohol substitutes not meant for human consumption (e.g., rubbing alcohol, mouthwash, and illegally produced homemade alcohol), and/or who drink beverage alcohol (e.g., beer and wine) in a way that is criminalized, like in unsanctioned public spaces [ 6 , 7 ]. Illicit drinkers’ use of public space is a result of visible poverty, namely, housing precarity, the gradual worsening of Vancouver’s housing crisis, the commonality of residing in Single Room Occupancy hotels (SROs) without common areas for socialising, intensive policing, and closure of neighbourhood parks.…”
Section: Illicit Drinking and Alcohol-related Harm In The Dtesmentioning
confidence: 99%
“…To avoid dangerously acute alcohol withdrawal symptoms, drinkers in the DTES often choose to consume harmful non-beverage alcohol substitutes, because they are cheaper and more geographically accessible than affordable beverage alcohol in the neighbourhood [ 7 , 8 ]. Drinkers’ structural marginalization is reflected by extremely high risk of drug poisoning death, emergency department use, police harassment, adulterant poisoning, hepatic injury, experience of interpersonal violence, robbery, accidents, hypothermia, dehydration, and traffic-related injury amongst our membership [ 6 – 8 ]. The ongoing violence of settler colonialism is a key driver of these and other alcohol-related harms for our membership, 80% of whom identify as Indigenous [ 8 ].…”
Section: Illicit Drinking and Alcohol-related Harm In The Dtesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research that evaluates the social and scienti c impact of North America's longest and largest drug user advocacy group, the Vancouver Area Network of Drug Users (VANDU), has demonstrated that PWUDs are capable of collectively advocating for health and wellbeing of marginalized groups [17]. Furthermore, prior ethnographic studies have noted that PWUDs through VANDU and its a liate drug user lead groups have the capacity to not only advocate and give voice to the most marginalized members of society, but they have the capability to transform the discriminatory rhetoric around the war on drugs [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%